2013
DOI: 10.1002/ajmg.a.35805
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal brain and skull growth in an Apert syndrome mouse model

Abstract: Craniofacial and neural tissues develop in concert throughout pre- and postnatal growth. FGFR-related craniosynostosis syndromes, such as Apert syndrome (AS), are associated with specific phenotypes involving both the skull and the brain. We analyzed the effects of the FGFR P253R mutation for Apert syndrome using the Fgfr2+/P253R mouse to evaluate the effects of this mutation on these two tissues over the course of development from day of birth (P0) to postnatal day 2 (P2). Three-dimensional magnetic resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 64 publications
4
26
0
Order By: Relevance
“…Evidence of semi-autonomous changes in the brain and skull is also provided by mutant mice. Models for Apert syndrome, for example, show that both structures display a relative dissociation in their size at early postnatal stages, which is interpreted in terms of stronger effects of the mutation on the skull than on the brain PRENATAL DEVELOPMENT OF SKULL AND BRAIN (Hill et al, 2013). According to our results, the environmental perturbation induced here has a similar effect on prenatally growing brain and skull size, showing the generalized effect of maternal malnutrition on these tissues.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Evidence of semi-autonomous changes in the brain and skull is also provided by mutant mice. Models for Apert syndrome, for example, show that both structures display a relative dissociation in their size at early postnatal stages, which is interpreted in terms of stronger effects of the mutation on the skull than on the brain PRENATAL DEVELOPMENT OF SKULL AND BRAIN (Hill et al, 2013). According to our results, the environmental perturbation induced here has a similar effect on prenatally growing brain and skull size, showing the generalized effect of maternal malnutrition on these tissues.…”
Section: Discussionsupporting
confidence: 64%
“…After studying a model for craniosynostosis, Aldridge et al (2010) concluded that the processes underlying alterations of the vault are relatively independent from those causing brain dysmorphologies. Hill et al (2013) also found a non-significant correlation between brain and skull morphology in mice at the time of birth, which is an ontogenetic stage very close to the late prenatal day analyzed in our study. However, they noted that this trend is altered in the immediately following days and two days after birth, when skull and brain morphology correlate significantly.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In animal models for human craniosynostosis syndromes, the abnormal skull shape can be detected before the premature closure of cranial vault sutures 71•, 72•]. The development of animal models for craniosynostosis [70, 73, 74] has already revealed many molecularly driven three-dimensional morphological changes in soft tissues of the head and skull that were not apparent in humans [71•, 75, 76•, 77]. These changes are more difficult to evaluate quantitatively in humans where observations are routinely made postnatally and there is a lack of appropriate morphological control data sets to make meaningful comparisons to abnormal phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In these conditions, mutations in fibroblast growth factor receptor (FGFR) genes cause cranial changes that obstruct flow of CSF and reduce absorption into the systemic circulation by increasing venous pressure [72, 73]. Mutations in these genes can also cause excessive growth of the brain itself, thereby compounding the problem [74-77]. Interestingly, hydrocephalus can accompany FGFR-associated skeletal dysplasias as well, likely reflecting the same underlying mechansims.…”
Section: Hydrocephalus Accompanied By Other Physical Features (Table 2)mentioning
confidence: 99%